A decade of challenges: ten-year analysis of non-tuberculous Mycobacteria infections in Vojvodina, Serbia - Kovačević, Dragica; Ilić, Miroslav; Vujičić, Emilija; Miljković, Dejan; Javorac, Jovan; Stjepanović, Mihailo; Savić, Nevena; Đekić, Dejan; Živanović, Dejan; Kovač, Milutin (The Journal of Infection in Developing Countries, 2025)
Introduction: Non-tuberculous mycobacteria (NTM) are a diverse group of environmental microorganisms, most non-pathogenic. Most people come into contact with NTM during their lives. Still, the infection occurs in people with previous lung comorbidities, weakened immune systems, and the elderly. This study aims to analyze the clinical characteristics of patients with NTM. Methodology: The research was conducted in the form of a retrospective study, which included 23 patients with a diagnosis of NTM who were treated at the Clinic for Tuberculosis and Interstitial Lung Diseases of the Institute of Pulmonary Diseases of Vojvodina in Sremska Kamenica from 2014 to 2023. Results: Patients were predominantly male (15, 65.2%). The most common type of NTM was Mycobacterium xenopi in 8 patients (34.8%), as well as the way of establishing the diagnosis in patients who had negative direct microscopy and culture confirmation (12, 52.2%), followed by positive direct microscopy and culture confirmation (10, 43.5%). Smokers were the most frequent (10, 55.6%). The most common comorbidity was chronic obstructive pulmonary disease (10, 43.5%). A statistically significant difference was found in the frequency of the method of proof across different types of non-tuberculous mycobacterium infections (Fisher's exact test = 21.928; p = 0.006). Fatal outcomes were seen in 17.6% of patients. Conclusions: A detailed history, evaluation of clinical features, radiological findings, and microbiological samples are required in patients with suspected NTM infection. Raising suspicion and speeding up diagnostic procedures in these patients is of great importance for the timely initiation of treatment and reduction of mortality.